CD and FTIR spectroscopic studies of carbohydrate-modified opioid peptides - Vass, Elemér (Array, 2008)
Abstract: The variety of vital functions played by glycoproteins in many physiological and pathological processes inspired the design of glycopeptides and the study of the effect of glycosylation on conformation. This work reports comparative circular dichroism (CD) and Fourier transform infrared (FTIR) spectroscopic studies on linear and cyclic Amadori and imidazolidinone-type glycopeptides 3–8 in comparison with spectroscopic data of the non-modified flexible parent peptides, Leu-enkephalin (H-Tyr-Gly-Gly-Phe-Leu-OH, 1) and its amide (H-Tyr-Gly-Gly-Phe- -Leu-NH2, 2). The CD and FTIR measurements were performed in different solvents in order to expose the structural and conformational differences caused by a keto-sugar, a rigid 5-membered imidazolidinone ring and/or cyclization. The combined application of CD and FTIR spectroscopy allowed to evaluate the relative amount of the extended and folded conformers of Amadori as well as imidazolidinone compounds and proved to be an effective tool for characterization of their structural features leading to a deeper understanding of their conformational behaviour